EMPOWERMENT OF VILLAGE LIBRARY IN INCREASING COMMUNITY READING INTEREST AS IMPLICATION OF DECREE OF THE MINISTER OF HOME AFFAIRS AND REGIONAL AUTONOMY NUMBER 3 OF 2001 : A Study As Dissemination Material For Library Observers On Community Service At Abimanyu Library, Tulangan, Sidoarjo Regency - BAKHTIYAR; FAHRIYAH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The study intends to describe: (1). Empowerment of village libraries as an implication of the implementation of the formation of village libraries. (2). The role of village libraries in increasing people's interest in reading (3). Constraints in increasing reading interest in rural communities. The research object is based on the village library empowerment content. The scope of research focuses on the realization of implementation management and the role of village libraries to increase people's interest in reading. This study uses a historical approach as a critical thinking analyst on social reality. Primary data as a primary source of information, data retrieval methods use a research library. The analysis uses descriptive qualitative analysis, relying on sources of analysis from various studies of literature containing theoretical, research and non-research studies. Observation is used to support theoretical constructs and content analysis to analyze the meaning of the concept of implementing the library formation in increasing reading interest in rural communities. The research results include; (1) Empowerment of Village Libraries is obliged to carry out as much as possible towards: (a). human Resource Management. (b). collection management. (c). service management. (d). marketing Management. (2). The role of village libraries in increasing people's interest in reading includes: (a). increase reading interest evenly in various regions. (b). become a place for learning activities. (c). support the improvement of literacy and reading skills (d). support increased information literacy. (3). Barriers to increasing reading interest in rural communities include: (a). access to information is still low. (b). the level of public education is still below standard. (c). generally low socioeconomic conditions. (d). library services are not evenly distributed. (e). appreciation and public response is still low.